Factors Associated with Knowledge of Teachers in the Agricultural University - K. T. Lahariya; N. R. Koshti (Journal of Agricultural Extension Management, 2025)
Knowledge is a pre requisite for successful performance in teaching and competency development. The present research has been undertaken to assess the level of knowledge possessed ·by teachers in the Agricultural University and to fl1Zd out the relationship between selected socio-personal and psychological characteristics and knowledge of the teachers. The study suggests that, to improve the knowledge of teachers, need based training must be imparted followed by proper ·evaluation, availability of modern instructional aids with skills in handling them. Associated job factors like achievement motivation, job satisfaction, job preference and favourable teaching attitude also need increased attention.